Effect of Financial Distress, Liquidity, and Leverage on the Audit Opinion Going Concern on Companies Listed on IDXESGL During the Pandemic Period (2019-2021) - Irma Suryani; Rita Yuniarti; Muhammad Syahrudin (Research Collaboration Community (RCC), 2023)
The Covid-19 pandemic has caused many companies to have significant losses that affect their going concern and opinions from auditors about it, such as the case of KAP Satrio Bing, Eny (SBE) and partners, affiliated Deloitte Indonesia for not providing a audit opinion going concern on SNP's finances, where the condition of the company`s increase debt and repayment failure, so due to financial difficulties they committed fraud by manipulating financial statements. This study aims to examine the effect of financial distress, liquidity, leverage on audit opinion going concern partially on companies listed on IDXESGL during the pandemic (2019-2021). The method used is explanatory with a population of 30 companies listed on the IDX during the period 2019 to 2021 with a sample of 29 companies. The analytical technique used is logistic regression with a significance level of 5%. The results showed that liquidity had an effect on audit opinion going concern, while financial distress and leverage had no effect on audit opinion going concern. This audit opinion going concern can be avoided by managing current assets effectively so that they are able to meet their current liabilities. The results of this study are expected to provide contributions and considerations for auditors in issuing audit opinions going concern and for companies to determine indicators that affect their going concern.